The Effect of Regulation and Organizational Commitment on the Successful Handling of Covid-19 with Job Satisfaction Mediation - Budiman, Bestari Jaka; Hartati,; Khairani, Emilia Nissa; Menola, Citra Ayu (International Journal of Statistics in Medical Research, 2024)
This study was intended to determine the effect of DPJP Job Satisfaction Mediating the Effect of Regulation and Work Commitment on the Successful Handling of Covid-19. The smart PLS 3.0 application is used to help analyze this research. All the p-values of the direct relationship variables were below 0.05, except for DPJP's job satisfaction on the successful handling of COVID-19, the p-value was above 0.05. Meanwhile, all p-values of indirect relationships are above 0.05. Government regulation and organizational commitment directly influence the success of handling covid-19, except that DPJP job satisfaction does not directly influence the success of handling covid-19. Meanwhile, the relationship between government regulation and organizational commitment to the successful handling of COVID-19 mediated by DPJP job satisfaction did not have a significant effect.